Efektifitas Penurunan Suhu Tubuh Subfebris Pada Anak Kejang Demam Dengan Menggunakan Kompres Hangat Di Ruang Rawat Inap Gardenia RSUD M.Sani - Dwi Gina Vita; Indah Purnama Sari; Yulianti Wulandari (Jurnal Medika Husada, 2023)
Fever in children is largely the result of changes in the heat center (thermoregulation) in the hypothalamus. Diseases characterized by fever can attack the body's systems. The problem of febrile seizures in children can have a big impact on early childhood. Treating fever so that it doesn't cause seizures can be done using non-pharmacological methods which are very easy and familiar. One way to treat fever is by giving a warm compress. This study aims to determine the effectiveness of reducing subfebrile body temperature in children with febrile convulsions using warm compresses in the Gardenia Inpatient Room, M.Sani Regional Hospital. The design of this research is a quasi-experimental without control group design. The sample in this study was 23 children with febrile seizures in the Gardenia Inpatient Room at M.Sani Regional Hospital, using probability sampling techniques. Data were analyzed using the Wilcoxon rank test. The results are known to show that there is effectiveness in reducing subfebrile body temperature in children with febrile seizures by using warm compresses in the Gardenia Inpatient Room at M.Sani Hospital with a p-value of 0.00. This research recommends that hospital nurses continue to carry out warm compress activities to help reduce fever in toddlers with febrile seizures and make it a mandatory nursing management in hospitals when treating children with fever.